S6 The profiles of JMJD3, UTX and H3K27me3 expression in pulmonary vasculature in rat MCT model of PAH and human iPAH: implications for pulmonary arterial hypertension. (12th November 2015) - Shao, D; Garfied, BE; Crosby, A; Young, P; Perros, F; Humbert, M; Adcock, IM; Morrell, N; Wort, SJ
Abstract : Introduction and objectives: There is increasing interest in the role of epigenetic gene regulation in the pathogenesis of pulmonary arterial hypertension (PAH), a condition associated with pulmonary vascular cell proliferation. Methylation on histone H3K27 (H3K27me3) has been found to be a key regulator of development and cell homeostasis. Methylation at H3K27 can be reversed by the Jumonji C (JmjC) domain-containing proteins, JMJD3 and UTX. Methods: Immunohistochemistry for JMJD3, UTX and H3K27me3 was performed on lungs from a monocrotoline (MCT) rat model of PAH, in control animals and in patients with idiopathic PAH and healthy control subjects. Results: In the rat MCT model of PAH, we found that the expression of JMJD3 protein is increased in all three cell layers (endothelial cells, smooth muscle cells and fibroblasts) in remodelled pulmonary arterioles (PA). The greatest increase is within endothelial cells, particularly in partially occluded or completely occluded PA (Appendix Figure 1 ). In contrast, the expression of UTX is unchanged. There was a corresponding decrease in H3K27me3 staining in remodelled PA and some cells completely lost H3K27me3 expression. JMJD3 protein expression was also found in remodelled PA in the lung of patients with iPAH especially in endothelial cells and the plexiform lesion. Conclusion: Our data suggest that JMJD3 expression and H3K27 histone methylation could play an important role in the pathogenesis of iPAH. The rat MCT model of PAH is a suitable model for further mechanistic and intervention studies.